Narrative, apparatus, ideology : a film theory reader - Rosen, Philip (Columbia University Press, 1986)
Smartly selected and organized, the essays in this anthology introduce several central issues in film theory, namely, the classical narrative text, oppositional and avant-garde cinema, subject positioning, the cinematic apparatus, and ideology. Written by seminal scholars, including Christian Metz, Jean-Louis Baudry, Stephen Heath, Peter Wollen, Laura Mulvey, and Noël Burch, as well as such leading thinkers as Roland Barthes, Julia Kristeva, and Jean-François Lyotard, these works utilize a number of approaches in their analyses, particularly structuralism, poststructuralism, psychoanalysis, feminism, neoformalism, Marxism, and semiotics. Divided into sections, the anthology features introductions to each group of essays outlining the major assumptions, ideas, and arguments of the articles and situating them within the history of film theory, narrative analysis, and social and cultural theory.